Electrolyte, battery containing electrolyte and electric device

By using additives and other additives such as halogen benzene compounds in lithium -ion battery electrolytes, a stable SEI film is generated on the surface of the litterian negative poles, which solves the problem of stable SEI on the surface of the existing electrolyte on the surface of the graphite. Stability and Kulun efficiency.

CN119361834AActive Publication Date: 2025-01-24ZHEJIANG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411908254.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

It is difficult for existing lithium-ion battery electrolytes to form a stable solid electrolyte interface (SEI) on the surface of graphite negative electrodes, resulting in poor capacity attenuation and cycling performance.

Method used

The electrolytic solution containing the halogen pedazine compound, double (halogen benzene) or halogen -containing sulfur -containing compounds is used as additives, and stable SEI membranes are restored by priority to the litteria negative.

Benefits of technology

The compatibility between the electrolyte and the graphite anode is achieved, the Coulombic efficiency and cycle life of the battery are improved, and the matching performance of the electrolyte and the graphite anode is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361834A_ABST
    Figure CN119361834A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte, a battery containing the electrolyte and a power utilization device, and belongs to the technical field of electrolyte for batteries. Comprising a lithium salt, a solvent and an additive, and the additive is a halogenated biphenyl derivative, a bis (halogenated phenyl) compound or a halogenated sulfur-containing heterocyclic compound. When the electrolyte is used for the battery, electrolyte decomposition and reducing gas generated by side reaction are effectively inhibited. The SEI membrane can prevent solvent molecules from being embedded into graphite and improve the coulombic efficiency and the cycling stability of the battery, so that the reversibility of electrolyte in a graphite negative electrode is improved. In the lithium ion battery, the electrolyte effectively improves the compatibility of a graphite negative electrode and a solvent, has excellent cycle life and high coulombic efficiency, and further improves the comprehensive electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an electrolyte and a battery and an electrical device containing the electrolyte, belonging to the technical field of battery electrolytes. Background Art

[0002] Lithium-ion batteries (LIBs) have become the preferred energy storage system for electric vehicles and portable electronic devices due to their high specific energy, low self-discharge, good cycle characteristics, no memory effect and environmental friendliness. The core structure of lithium-ion batteries covers positive electrode materials, negative electrode materials, electrolytes, separators and metal casings. Among them, the positive and negative electrodes play a key role in the operation of the battery, responsible for the storage and release of lithium ions. Graphite has a high theoretical specific capacity (372mAh / g), a low working potential (~0.1 V vs. Li / Li + ) and good structural stability (volume change <10%), and is currently the most widely used negative electrode material in the lithium-ion battery market.

[0003] Currently, commercial lithium-ion battery electrolytes generally use electrolytes based on ethylene carbonate (EC) solvent systems. EC molecules can preferentially undergo reduction and decomposition on the surface of graphite negative electrodes to form a stable solid electrolyte interface (SEI), thereby achieving reversible insertion / extraction of lithium ions in the graphite negative electrode. However, EC-based electrolytes have high melting points (38 °C) and poor oxidation stability (<4.3 V vs. Li / Li + ) and crosstalk between electrodes, which limits the application range of LIBs. Propylene carbonate (PC) is a solvent with a high dielectric constant and a wide liquid phase range, a low freezing point, a wide temperature range, strong solvation ability and a high flash point (132 °C). In addition, it also has high negative electrode stability and good compatibility with high nickel positive electrodes. However, when paired with graphite negative electrodes, PC is difficult to form a stable SEI layer on the graphite surface due to its large molecular size and different reduction decomposition pathways, resulting in its violent decomposition at the negative electrode interface. This poor interfacial behavior can lead to severe capacity decay, which limits the practical application of PC in lithium-ion batteries. In addition to PC, many ether and amine solvents also have poor compatibility with graphite anodes, such as dimethoxyethane (DME), N,N-dimethylformamide (DMF) and dioxolane (DOL). The development of an electrolyte system that is compatible with graphite negative electrodes and has excellent electrochemical properties is of great significance for realizing wide temperature range and high-performance lithium-ion batteries.

[0004] Researchers have successfully overcome the poor compatibility of PC solvents with graphite anodes by increasing the concentration of lithium salts to form highly concentrated electrolytes (HCEs) or introducing diluents to construct locally high concentration electrolytes (LHCEs). However, practical applications still face many challenges such as high cost, environmental impact, and long-term stability. In contrast, the use of electrolyte additives is a more cost-effective and environmentally friendly solution. Additives can be preferentially reduced in the electrolyte to form a stable SEI layer on the surface of the anode, thereby realizing the reversible cycle of LIBs based on PC solvent electrolytes. This strategy can not only reduce the overall cost of the electrolyte, but also has good practical application prospects. However, the application effect of additives disclosed at present is not ideal, especially in terms of cycle performance and compatibility with the anode. Summary of the invention

[0005] In view of this, the present application first provides an electrolyte, which aims to achieve compatibility between the electrolyte and the graphite negative electrode by preferentially reducing the graphite negative electrode to generate a stable SEI film, while having good coulombic efficiency and cycle life.

[0006] Specifically, the present application is implemented through the following scheme: An electrolyte comprises a lithium salt, a solvent and an additive, wherein the mass percentage of the additive in the electrolyte is not less than 0.1%, and the additive comprises a first type of additive and a second type of additive.

[0007] The first type of additives are halogenated biphenyl compounds or bis(halogenated phenyl) compounds, The structural formula of the halogenated biphenyl compound satisfies: , wherein X is selected from H atoms, halogen atoms or haloalkyl groups (not all X atoms are H atoms), The structural formula of the bis(halogenated phenyl) compound satisfies: , wherein X is selected from H atom, halogen atom or halogenated alkyl (X cannot all be H atoms), and R is selected from any one of alkyl, carbonate, sulfate, sulfonate, sulfite, and halogenated phenyl.

[0008] The second type of additive is a halogenated sulfur-containing heterocyclic compound, and the structural formula of the halogenated sulfur-containing heterocyclic compound satisfies: , wherein R is selected from CH, CX or N, and X is selected from H, a halogen atom or a haloalkyl group. (X cannot all be H).

[0009] Further, as a preference: Among the first type of additives, When X is a halogen atom, the number of the halogen atoms is 2-10; when X is a haloalkyl group, the number of the halogen atoms in the haloalkyl group is 1-3.

[0010] The first type of additives are decafluorobiphenyl, nonafluorobiphenyl, octafluorobiphenyl, heptafluorobiphenyl, hexafluorobiphenyl, pentafluorobiphenyl, tetrafluorobiphenyl, trifluorobiphenyl, decachlorobiphenyl, nonachlorobiphenyl, octachlorobiphenyl, heptachlorobiphenyl, hexachlorobiphenyl, pentachlorobiphenyl, tetrachlorobiphenyl, trichlorobiphenyl, dichlorobiphenyl, 2-bromo-4'-chloro-1,1'-biphenyl, 4-bromo-2-fluorobiphenyl, 3'-fluoro-2,4,6-trichlorobiphenyl, 3'-fluoro-2,4,4'-trichlorobiphenyl, 2',4'-dichloro-3,5-difluorobiphenyl, 2',3'-dichloro-3,5-difluorobiphenyl, 4-bromo-2,3-dichloro-4'-fluoro-1,1'-biphenyl, 2',3'-dichloro-3,4- At least one of difluorobiphenyl, 3-fluoro-2,2',5-trichlorobiphenyl, 3'-fluoro-2,3,4'-trichlorobiphenyl, 2',4'-dichloro-2,5-difluorobiphenyl, 5-bromo-2'-chloro-2,4,6'-trifluoro-1'-biphenyl, 2',3'-dichloro-2,3,4,5-tetrafluorobiphenyl, 2',4'-dichloro-2,3,4,5-tetrafluorobiphenyl, dibromooctafluorobiphenyl, 3-chloro-4'-(trifluoromethyl)-1,1'-biphenyl, 4-(trifluoromethyl)-biphenyl, tetradecafluoroterphenyl, bis(pentafluorophenyl)methane, bis(pentafluorophenyl)carbonate, pentafluorophenyl pentafluorobenzenesulfonate, dipentafluorophenyl sulfate, and dipentafluorophenyl sulfite. More preferably, it is at least one selected from decafluorobiphenyl, 2-bromo-4'-chloro-1,1'-biphenyl, and bis(pentafluorophenyl) carbonate.

[0011] In the second type of additives, when X is a halogen atom, the number of the halogen atoms is 2-4; when X is a haloalkyl group, the number of the halogen atoms in the haloalkyl group is 1-3.

[0012] The second type of additives are 2-fluorothiophene, 3-fluorothiophene, 2,3-difluorothiophene, 2,4-difluorothiophene, 2,5-difluorothiophene, 3,4-difluorothiophene, 2,3,4-trifluorothiophene, 2,3,5-trifluorothiophene, 2,4,5-trifluorothiophene, 2,3,4,5-tetrafluorothiophene, 2-chlorothiophene, 3-chlorothiophene, 2,3-dichlorothiophene, 2,4-dichlorothiophene, 2,5-dichlorothiophene, 3,4-dichlorothiophene, 2,3,4-trichlorothiophene, 2,3,5-trichlorothiophene, 2,4,5-trichlorothiophene, 2,3,4,5-tetrachlorothiophene, 2-bromothiophene, 3-bromothiophene, 2,3-dibromothiophene, 2,4-dibromothiophene, 2,5-dibromothiophene, 3,4- 4-Dibromothiophene, 2,3,4-Tribromothiophene, 2,3,5-Tribromothiophene, 2,4,5-Tribromothiophene, 2,3,4,5-Tetrabromothiophene, 2-Chloro-4-fluoro-thiophene, 2-Chloro-4-fluoro-thiophene, 4-Chloro-2-fluoro-thiophene, 2-Chloro-3-fluoro-thiophene, 2-Chloro-5-fluoro-thiophene, 3-Bromo-2-fluoro-thiophene, 2-Bromo-3-fluoro-thiophene, 2-Bromo-4-fluoro-thiophene, 4-Bromo-2-fluoro-thiophene, 5-Bromo-2-fluoro-thiophene, 3-Bromo-4-fluoro-thiophene, 3-Bromo-2-chlorothiophene, 2-Bromo-3-chloro-thiophene, 2-Bromo-4-chloro-thiophene, 4-Bromo-2-chloro-thiophene, 2-Bromo-5-chloro-thiophene, 3-Bromo-4-chloro-thiophene, 3-bromo-2,5-dichlorothiophene, 4-bromo-3-chloro-2-fluoro-thiophene, 3,4-dibromo-2-chloro-thiophene, 3,5-dibromo-2-chloro-thiophene, 4-bromo-2,3-dichlorothiophene, 3,4-dibromo-2,5-dichlorothiophene, 4,5-dichloro-2-fluoro-1,3-thiazole, 2,4-dichlorothiazole, 2,4,5-trichlorothiazole, 2,4,5-tribromothiazole, 5-(difluoromethyl)-2,4-difluoro-thiophene, 2,5-difluoro-1,3,4-thiadiazole, 2,5- At least one of dichloro-1,3,4-thiadiazole, 2,5-dibromo-1,3,4-thiadiazole, 2-chloro-5-fluoro-1,3,4-thiadiazole, 2-bromo-5-fluoro-1,3,4-thiadiazole, 2-bromo-5-chloro-1,3,4-thiadiazole, 2,5-bis(trifluoromethyl)-1,3,4-thiadiazole, 2,5-bis(1,1,2,2,2-pentafluoroethyl)-1,3,4-thiadiazole, and 2,5-bis(1,1,2,2,2-pentafluoroethyl)-1,3,4-thiadiazole. More preferably, at least one of 2,3,4,5-tetrachlorothiophene and 2,4-dichlorothiazole.

[0013] The above-mentioned halogen atom is F, Cl or Br.

[0014] The mass percentage of the additive in the electrolyte is 0.4-10%, preferably 0.7-5.0%.

[0015] The lithium salt is any one of inorganic anion lithium salts and organic anion lithium salts such as lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium oxalate borate (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4). More preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0016] The lithium salt concentration is 0.1-6.0 mol / L. More preferably, the lithium salt concentration in the electrolyte is 0.6-1.5 mol / L. Preferably, it is 1.0-1.5 mol / L.

[0017] The solvents are dimethoxyethane (DME), N,N-dimethylformamide (DMF), propylene carbonate (PC) and 1,3-dioxolane (DOL).

[0018] The second object of the applicant is to provide a battery containing the above-mentioned characteristic electrolyte, including a positive electrode active material, a negative electrode active material and an electrolyte, wherein the positive electrode active material is a ternary positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), lithium cobalt oxide positive electrode material (LiCoO2), lithium manganese oxide positive electrode material (LiMnO2) or lithium iron phosphate positive electrode material (LiFePO4), and the negative electrode active material is artificial graphite, natural graphite or composite graphite.

[0019] The third object of the applicant is to provide an electrical device including a battery having the above-mentioned characteristics.

[0020] When the electrolyte of the present application is used in lithium-ion batteries, its advantages and technical effects are as follows: 1. In the embodiment of the present invention, halogenated biphenyl compounds, bis(halogenated phenyl) compounds, and halogenated sulfur-containing heterocyclic compounds are used, and their preferential reduction characteristics on the graphite negative electrode are utilized to generate a stable solid electrolyte interface film (SEI) on the graphite surface during the charge and discharge process. The SEI film has high chemical and electrochemical stability, can effectively block the further embedding of solvent molecules, and allow lithium ions to pass smoothly to maintain ionic conductivity. The halogen atoms or halogenated alkyl groups in the additives form fluorine-, chlorine-, or bromine-containing compounds when reduced on the electrode surface. These compounds, as the main components of the SEI film, enhance the reduction resistance and barrier properties of the SEI film. The biphenyl and phenyl compounds in the first type of additives can improve the mechanical strength of the SEI film due to their rigid structure, prevent it from breaking or dissolving during the cycle, and further improve the cycle stability and coulomb efficiency of the battery. The second type of additives can form a sulfur- and nitrogen-containing SEI film on the surface of the negative electrode. The generated SEI film is dense and has high thermal stability, and reduces the interface impedance, thereby improving the battery cycle performance.

[0021] 2. The electrolyte of the present invention can effectively improve the matching performance between the electrolyte and the graphite negative electrode; 3. The electrolyte of the present invention has excellent compatibility with the positive electrode, achieving a long cycle life and high coulombic efficiency of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of the electrolyte prepared in Example 1. Figure 1 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 1, Figure 1 (c) is the LiNi electrolyte prepared in Example 1 0.8 Co 0.1 Mn 0.1 O2||Cycle life curve in graphite battery; Figure 2 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of the electrolyte prepared in Example 2. Figure 2 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 2, Figure 2 (c) is the LiNi electrolyte prepared in Example 2 0.8Co 0.1 Mn 0.1 O2||Cycle life curve in graphite battery; Figure 3 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of the electrolyte prepared in Example 3. Figure 3 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 3, Figure 3 (c) is the electrolyte prepared in Example 3 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Cycle life curve in graphite battery; Figure 4 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Example 4. Figure 4 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 4, Figure 4 (c) is the electrolyte prepared in Example 4 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Cycle life curve in graphite battery; Figure 5 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Example 5, Figure 5 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 5; Figure 6 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of the electrolyte prepared in Example 6, Figure 6 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 6, Figure 6 (c) is a charge and discharge curve of the electrolyte prepared in Example 6 in a LiFePO4||graphite battery; Figure 7 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Example 7, Figure 7 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 7, Figure 7 (c) is the electrolyte prepared in Example 7 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Cycle life curve in graphite battery; Figure 8(a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Example 8, Figure 8 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Example 8, Figure 8 (c) is a charge and discharge curve of the electrolyte prepared in Example 8 in a LiFePO4||graphite battery; Fig. 9 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Comparative Example 1, Fig. 9 (b) is the electrolyte prepared in Comparative Example 1 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Charge and discharge curves in graphite battery, Fig. 9 (c) is a charge and discharge curve of the electrolyte prepared in Comparative Example 1 in a LiFePO4||graphite battery; Fig.10 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Comparative Example 2. Fig.10 (b) is the electrolyte prepared in Comparative Example 2 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Charge and discharge curves in graphite battery; Fig.11 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Comparative Example 3, Fig.11 (b) is the electrolyte prepared in Comparative Example 3 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Charge and discharge curves in graphite battery; Fig.12 (a) is a charge-discharge curve of a graphite||Li asymmetric battery of an electrolyte prepared in Comparative Example 4, Fig.12 (b) is a cycle life curve of the graphite||Li asymmetric battery of the electrolyte prepared in Comparative Example 4, Fig.12 (c) is a charge and discharge curve of the electrolyte prepared in Comparative Example 4 in a LiFePO4||graphite battery. Fig.12 (d) is the electrolyte prepared in Comparative Example 4 in LiNi 0.8 Co 0.1 Mn 0.1 O2||Cycle life curve in graphite battery.

[0024] In the above cycle life curve, the upper line corresponds to the changing trend of the coulomb efficiency in the right vertical axis, and the lower line corresponds to the changing trend of the specific capacity in the left vertical axis. DETAILED DESCRIPTION

[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0026] Example 1 This embodiment provides an electrolyte, and its preparation method is as follows: Propylene carbonate and LiPF6 were mixed and stirred at room temperature until the lithium salt was completely dissolved. Then 1 wt% of decafluorobiphenyl was added and stirred until the electrolyte was clear. The prepared electrolyte had a lithium salt concentration of 1.0 mol / L.

[0027] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 1 shown.

[0028] Figure 1 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.2 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0029] Figure 1 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 1.50 mAh·cm -2 , the test voltage range is 0.001 V~1.0 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.2 C long cycle. It can be seen that after 150 cycles, the capacity retention rate of the above electrolyte is 93.66%, and the average coulombic efficiency is close to 100%.

[0030] Figure 1 (c) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 1.7 mAh cm -2The test voltage range is 2.8 V~4.55 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the above electrolyte can still maintain a capacity of 99% after 200 cycles, and the average coulombic efficiency is close to 100%. This shows that the additive can effectively prevent the decomposition of the electrolyte.

[0031] Example 2 This embodiment provides an electrolyte, and its preparation method is as follows: Propylene carbonate was mixed with LiFSI and stirred at room temperature until the lithium salt was completely dissolved. Then 1 wt% of trichlorobiphenyl was added and stirred until the electrolyte was clear. The prepared electrolyte had a lithium salt concentration of 1.0 mol / L.

[0032] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 2 shown.

[0033] Figure 2 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.2 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0034] Figure 2 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 1.80 mAh·cm -2 , the test voltage range is 0.001 V~1.5 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.2 C long cycle. It can be seen that after 150 cycles of the above electrolyte, the capacity retention rate is 94.27%, and the average coulombic efficiency is close to 100%.

[0035] Figure 2 (c) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 2.1 mAh cm -2 The test voltage range is 2.8 V~4.55 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the above electrolyte can still maintain a capacity retention rate of 95.5% after 200 cycles, and the average coulombic efficiency is close to 100%. This shows that the additive can effectively prevent the decomposition of the electrolyte.

[0036] Example 3 This embodiment provides an electrolyte, and its preparation method is as follows: Mix dimethoxyethane with an appropriate amount of LiPF6 and stir at room temperature until the lithium salt is completely dissolved. Then add 1.5 wt% of 2-bromo-4'-chloro-1,1'-biphenyl and continue stirring until the electrolyte is clear. The prepared electrolyte has a lithium salt concentration of 1.2 mol / L.

[0037] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 3 shown.

[0038] Figure 3 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0039] Figure 3 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 1.80 mAh·cm -2 , the test voltage range is 0.001 V~1.0 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.5 C long cycle. It can be seen that after 150 cycles, the capacity retention rate of the above electrolyte is 98.25%, and the average coulombic efficiency is close to 100%.

[0040] Figure 3 (c) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 1.7 mAh cm -2 The test voltage range is 2.8 V~4.55 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the above electrolyte can still have a capacity retention rate of 94.5% after 200 cycles, and the average coulombic efficiency is close to 100%. This shows that the additive can effectively prevent the decomposition of the electrolyte.

[0041] Example 4 This embodiment provides an electrolyte, and its preparation method is as follows: Dimethoxyethane was mixed with an appropriate amount of LiTFSI and stirred at room temperature until the lithium salt was completely dissolved. Then 3 wt% of 4-bromo-2-fluorobiphenyl was added and stirred until the electrolyte was clear. The lithium salt concentration of the prepared electrolyte was 1.5 mol / L.

[0042] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 4 shown.

[0043] Figure 4 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0044] Figure 4 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 2.2 mAh·cm -2 , the test voltage range is 0.001 V~1.5 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.5 C long cycle. It can be seen that after the above electrolyte is cycled for 150 cycles at 0.5 C rate, the average coulombic efficiency is close to 100%.

[0045] Figure 4 (c) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 1.9 mAh cm -2 The test voltage range is 2.8 V~4.55 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the above electrolyte can still have a capacity retention rate of 93.6% after 200 cycles, and the average coulombic efficiency is close to 100%. This shows that the additive can effectively prevent the decomposition of the electrolyte.

[0046] Example 5 This embodiment provides an electrolyte, and its preparation method is as follows: Propylene carbonate was mixed with an appropriate amount of LiBOB and stirred at room temperature until the lithium salt was completely dissolved. Then 4 wt% of 4-(trifluoromethyl)-biphenyl was added and stirred until the electrolyte was clear. The prepared electrolyte had a lithium salt concentration of 1 mol / L.

[0047] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 5 shown.

[0048] Figure 5 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.2 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0049] Figure 5 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 2.4 mAh·cm -2 , the test voltage range is 0.001 V~1.0 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.2 C long cycle. It can be seen that after the above electrolyte is cycled for 150 cycles at 0.2 C rate, the average coulombic efficiency is close to 100%.

[0050] Example 6 This embodiment provides an electrolyte, and its preparation method is as follows: Mix N,N-dimethylformamide with an appropriate amount of LiPF6 and stir at room temperature until the lithium salt is completely dissolved. Then add 5 wt% of bis(pentafluorophenyl) carbonate and continue stirring until the electrolyte is clear. The prepared electrolyte has a lithium salt concentration of 1.3 mol / L.

[0051] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 6 shown.

[0052] Figure 6 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0053] Figure 6 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 1.80 mAh·cm -2 , the test voltage range is 0.001 V~1.0 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.5 C long cycle. It can be seen that after the above electrolyte is cycled for 150 cycles at 0.5 C rate, the average coulombic efficiency is 99.94%, close to 100%.

[0054] Figure 6 (c) is the electrolyte used for LiFePO4||graphite battery testing, where the surface capacity of the LiFePO4 electrode is 2.1 mAh·cm -2 The test voltage range is 2.8 V~3.8 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the voltage platform of LiFePO4 and graphite remains stable, showing good electrochemical kinetic performance.

[0055] Example 7 This embodiment provides an electrolyte, and its preparation method is as follows: Propylene carbonate was mixed with an appropriate amount of LiPF6 and stirred at room temperature until the lithium salt was completely dissolved. Then 0.7 wt% of 2,3,4,5-tetrachlorothiophene was added and stirred until the electrolyte was clear. The prepared electrolyte had a lithium salt concentration of 1.0 mol / L.

[0056] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 7 shown.

[0057] Figure 7 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.2 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0058] Figure 7 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 1.80 mAh·cm -2 , the test voltage range is 0.001 V~1.0 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.2 C long cycle. It can be seen that after the above electrolyte is cycled for 150 cycles at 0.2 C rate, the average coulombic efficiency is close to 100%.

[0059] Figure 7 (c) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 1.8 mAh cm -2 The test voltage range is 2.8 V~4.55 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the above electrolyte can still have a capacity retention rate of 90.38% after 200 cycles, and the average coulombic efficiency is close to 100%. This shows that the additive can effectively prevent the decomposition of the electrolyte.

[0060] Example 8 This embodiment provides an electrolyte, and its preparation method is as follows: Mix N,N-dimethylformamide with an appropriate amount of LiPF6 and stir at room temperature until the lithium salt is completely dissolved. Then add 0.8 wt% of 2,4-dichlorothiazole and continue stirring until the electrolyte is clear. The prepared electrolyte lithium salt concentration is 1.0 mol / L.

[0061] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Figure 8shown.

[0062] Figure 8 (a) is the charge and discharge curve of the electrolyte in the graphite||Li battery, and the test rate is 0.1 C charge and discharge for 3 cycles, and 0.2 C charge and discharge for a long cycle. It can be seen that the above electrolyte can achieve efficient and reversible charge and discharge cycles.

[0063] Figure 8 (b) shows the cycle life curve of the electrolyte used in the graphite||Li battery, where the surface capacity of the graphite electrode is 1.80 mAh·cm -2 , the test voltage range is 0.001 V~1.0 V, and the test procedure is 0.1 C charge and discharge for three cycles, and 0.2 C long cycle. It can be seen that after the above electrolyte is cycled for 150 cycles at 0.2 C rate, the average coulombic efficiency is close to 100%.

[0064] Figure 8 (c) is the electrolyte used in LiFePO4||graphite battery testing, where the surface capacity of the LiFePO4 electrode is 2.3 mAh cm -2 The test voltage range is 2.8 V~3.8 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the voltage platform of LiFePO4 and graphite remains stable, showing good electrochemical kinetic performance.

[0065] Comparative Example 1 The electrolyte preparation method of this comparative example is as follows: An appropriate amount of LiPF6 is added to propylene carbonate, and the mixture is stirred and mixed until the lithium salt is completely dissolved and a clear electrolyte is obtained. In the prepared electrolyte, the concentration of LiPF6 is 1.0 mol / L.

[0066] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Fig. 9 shown.

[0067] Fig. 9 (a) is the charge and discharge image of the electrolyte in the graphite||Li asymmetric battery. It can be seen that the graphite negative electrode cannot achieve reversible charge and discharge in the propylene carbonate-based electrolyte, which indicates that propylene carbonate as a single solvent for the electrolyte is incompatible with the graphite negative electrode material.

[0068] Fig. 9 (b) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1The surface capacity of the O2 electrode is 2.0 mAh cm -2 , the test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the curve shows abnormal capacity performance and there is no obvious charge and discharge voltage platform, indicating that propylene carbonate as a single solvent electrolyte cannot support reversible charge and discharge of lithium-ion batteries.

[0069] Fig. 9 (c) is the electrolyte used for LiFePO4||graphite battery testing, where the surface capacity of the LiFePO4 electrode is 1.7 mAh·cm -2 The test voltage range is 2.8 V~3.8 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. It can be seen that the electrolyte cannot support the reversible charge and discharge of LiFePO4||graphite battery.

[0070] Comparative Example 2 The electrolyte preparation method of this comparative example is as follows: An appropriate amount of LiFSI was added to dimethoxyethane and stirred until the lithium salt was completely dissolved and a clear electrolyte was obtained. The concentration of LiFSI in the prepared electrolyte was 1.0 mol / L.

[0071] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Fig.10 shown.

[0072] Fig.10 (a) is the charge and discharge image of the electrolyte in the graphite||Li asymmetric battery. It can be seen that the graphite negative electrode cannot achieve reversible charge and discharge in the dimethoxyethane-based electrolyte, which indicates that dimethoxyethane as a single electrolyte solvent is incompatible with the graphite negative electrode material.

[0073] Fig.10 (b) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 2.2 mAh cm -2 The test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the curve shows abnormal capacity performance and there is no obvious charge and discharge voltage platform, indicating that dimethoxyethane as a single solvent electrolyte cannot support reversible charge and discharge of lithium-ion batteries.

[0074] Comparative Example 3 The electrolyte preparation method of this comparative example is as follows: An appropriate amount of LiTFSI is added to N,N-dimethylformamide, and the mixture is stirred until the lithium salt is completely dissolved and a clear electrolyte is obtained. In the prepared electrolyte, the concentration of LiTFSI is 1.0 mol / L.

[0075] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Fig.11 shown.

[0076] Fig.11 (a) is the charge and discharge image of the electrolyte in the graphite||Li asymmetric battery. It can be seen that the graphite negative electrode cannot achieve reversible charge and discharge in the N,N-dimethylformamide-based electrolyte, which indicates that N,N-dimethylformamide as a single electrolyte solvent is incompatible with the graphite negative electrode material.

[0077] Fig.11 (b) is the electrolyte for LiNi 0.8 Co 0.1 Mn 0.1 O2||Graphite battery test, including LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 2.1 mAh cm -2 , the test voltage range is 2.8 V~4.5 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the curve shows abnormal capacity performance and there is no obvious charge and discharge voltage platform, indicating that N,N-dimethylformamide as a single solvent electrolyte cannot support reversible charge and discharge of lithium-ion batteries.

[0078] Comparative Example 4 This comparative example is a commercial ester-based electrolyte, and the electrolyte preparation method is as follows: A certain amount of LiPF6 is slowly dissolved in ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, so that the concentration of lithium salt LiPF6 is 1 mol / L, thereby preparing a traditional commercial ester-based electrolyte.

[0079] The electrolyte solution with the above formula was used to test the battery's electrical performance. The results are as follows: Fig.12 shown.

[0080] Fig.12 (a) is a charge-discharge curve of a commercial ester-based electrolyte for a graphite||Li asymmetric battery. The test procedure is: 0.1 C charge-discharge three cycles followed by a 0.2 C long cycle. It can be seen that the reversibility of the charge-discharge process of this electrolyte is not as good as that of the electrolyte of the present invention.

[0081] Fig.12 (b) shows the cycle life curve of a graphite||Li asymmetric battery using a commercial ester-based electrolyte, where the surface capacity of the graphite electrode is 1.5 mAh cm -2 The test voltage range is 0.001 V~1.0 V, the test rate is 0.1 C charge and discharge for three cycles, and 0.2 C long cycle. It can be seen that the capacity retention rate of the electrolyte decreases significantly after 150 cycles.

[0082] Fig.12 (c) is a charge and discharge test curve of a commercial ester-based electrolyte for LiFePO4||graphite battery, where the surface capacity of the LiFePO4 electrode is 2.1 mAh·cm -2 The test voltage range is 2.8 V~3.8 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for a long cycle. It can be seen that the reversibility of the charge and discharge process of this electrolyte is poor.

[0083] Fig.12 (d) is a commercial ester-based electrolyte in LiNi 0.8 Co 0.1 Mn 0.1 O2|| Cycle life curve in graphite battery, where LiNi 0.8 Co 0.1 Mn 0.1 The surface capacity of the O2 electrode is 1.4 mAh cm -2 The test voltage range is 2.8 V~4.55 V, the test rate is 0.1 C charge and discharge for 3 cycles, and 0.5 C charge and discharge for long cycles. It can be seen that the capacity retention rate of the above electrolyte after 200 cycles is only 74.72%, and the cycle stability is not as good as the electrolyte of the present invention.

[0084] In the above embodiments, halogenated biphenyl compounds, bis(halogenated phenyl) compounds, and halogenated sulfur-containing heterocyclic compounds are used as additives. When the additives are used as electrolyte components in the charge and discharge process of the battery, a stable SEI film is generated on the graphite surface, which can effectively block the further embedding of solvent molecules, while allowing lithium ions to pass smoothly and maintain ionic conductivity. The first type of additives (such as Examples 1 to 6 above) biphenyls and their derivatives can improve the mechanical strength of the SEI film due to their rigid structure, prevent it from breaking or dissolving during the cycle, and further improve the cycle stability and coulomb efficiency of the battery. The second type of additives (such as Examples 7 and 8 above) can form a sulfur- and nitrogen-containing SEI film on the surface of the negative electrode. The generated SEI film is dense and has high thermal stability, and reduces the interfacial impedance, thereby improving the battery cycle performance. Compared with commercial ester-based electrolytes, the above electrolyte significantly improves the cycle stability and coulomb efficiency of the battery.

[0085] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.

Claims

1. An electrolyte, characterized in that: The electrolyte comprises a lithium salt, a solvent and an additive, wherein the mass percentage of the additive in the electrolyte is not less than 0.1%, and the additive is a halogenated biphenyl compound, a bis(halogenated phenyl) compound or a halogenated sulfur-containing heterocyclic compound. The structural formula of the halogenated biphenyl compound satisfies: , wherein X is selected from a H atom, a halogen atom or a haloalkyl group, The structural formula of the bis(halogenated phenyl) compound satisfies: , wherein X is selected from H atom, halogen atom or halogenated alkyl, and R is selected from any one of alkyl, carbonate, sulfate, sulfonate, sulfite and halogenated phenyl. The structural formula of the halogenated sulfur-containing heterocyclic compound satisfies: , wherein R is selected from CH, CX or N, and X is selected from H, a halogen atom or a haloalkyl group.

2. An electrolyte according to claim 1, characterized in that: The halogen atom is F, Cl or Br.

3. An electrolyte according to claim 1, characterized in that: The additive is decafluorobiphenyl, nonafluorobiphenyl, octafluorobiphenyl, heptafluorobiphenyl, hexafluorobiphenyl, pentafluorobiphenyl, tetrafluorobiphenyl, trifluorobiphenyl, decachlorobiphenyl, nonachlorobiphenyl, octachlorobiphenyl, heptachlorobiphenyl, hexachlorobiphenyl, pentachlorobiphenyl, tetrachlorobiphenyl, trichlorobiphenyl, dichlorobiphenyl, 2-bromo-4'-chloro-1,1'-biphenyl, 4-bromo-2-fluorobiphenyl, 3'-fluoro-2, 4,6-Trichlorobiphenyl, 3'-fluoro-2,4,4'-trichlorobiphenyl, 2',4'-dichloro-3,5-difluorobiphenyl, 2',3'-dichloro-3,5-difluorobiphenyl, 4-bromo-2,3-dichloro-4'-fluoro-1,1'-biphenyl, 2',3'-dichloro-3,4-difluorobiphenyl, 3-fluoro-2,2',5-trichlorobiphenyl, 3'-fluoro- 2,3,4'-Trichlorobiphenyl, 2',4'-dichloro-2,5-difluorobiphenyl, 5-bromo-2'-chloro-2,4,6'-trifluoro-1'-biphenyl, 2',3'-dichloro-2,3,4,5-tetrafluorobiphenyl, 2',4'-dichloro-2,3,4,5-tetrafluorobiphenyl, dibromooctafluorobiphenyl, 3-chloro-4'-(trifluoromethyl)-1,1'-biphenyl, 4-(trifluoromethyl)-biphenyl, tetradecafluoroterphenyl, bis(pentafluorophenyl)methane, bis(pentafluorophenyl)carbonate, pentafluorophenyl pentafluorobenzenesulfonate, dipentafluorophenyl sulfate, dipentafluorophenyl sulfite, 2-fluorothiophene, 3-fluorothiophene, 2,3-difluorothiophene, 2,4-difluorothiophene, 2,5-difluorothiophene, 3,4-difluorothiophene, 2,3,4-trifluorothiophene Fluorothiophene, 2,3,5-trifluorothiophene, 2,4,5-trifluorothiophene, 2,3,4,5-tetrafluorothiophene, 2-chlorothiophene, 3-chlorothiophene, 2,3-dichlorothiophene, 2,4-dichlorothiophene, 2,5-dichlorothiophene, 3,4-dichlorothiophene, 2,3,4-trichlorothiophene, 2,3,5-trichlorothiophene, 2,4,5-trichlorothiophene, 2,3,4 ,5-tetrachlorothiophene, 2-bromothiophene, 3-bromothiophene, 2,3-dibromothiophene, 2,4-dibromothiophene, 2,5-dibromothiophene, 3,4-dibromothiophene, 2,3,4-tribromothiophene, 2,3,5-tribromothiophene, 2,4,5-tribromothiophene, 2,3,4,5-tetrabromothiophene, 2-chloro-4-fluoro-thiophene, 2-chloro-4-fluoro-thiophene, 4 -Chloro-2-fluoro-thiophene, 2-chloro-3-fluoro-thiophene, 2-chloro-5-fluoro-thiophene, 3-bromo-2-fluoro-thiophene, 2-bromo-3-fluoro-thiophene, 2-bromo-4-fluoro-thiophene, 4-bromo-2-fluoro-thiophene, 5-bromo-2-fluoro-thiophene, 3-bromo-4-fluoro-thiophene, 3-bromo-2-chlorothiophene, 2-bromo-3-chloro-thiophene, 2-bromo-4-fluoro-thiophene. Chloro-thiophene, 4-bromo-2-chloro-thiophene, 2-bromo-5-chloro-thiophene, 3-bromo-4-chloro-thiophene, 3-bromo-2,5-dichlorothiophene, 4-bromo-3-chloro-2-fluoro-thiophene, 3,4-dibromo-2-chloro-thiophene, 3,5-dibromo-2-chloro-thiophene, 4-bromo-2,3-dichlorothiophene, 3,4-dibromo-2,5-dichlorothiophene, 4,5-dichloro-2-fluoro-1,3-thiazole, 2,4-dichlorothiazole, 2,4,5-trichlorothiazole, 2,4,5-tribromothiazole, 5-(difluoromethyl)-2,4-difluoro-thiophene, 2,5-difluoro-1,3,4-thiadiazole, 2,5-dichloro-1,3,4-thiadiazole, 2,5-dibromo-1,3,4-thiadiazole, 2-chloro-5-fluoro-1,3,4- At least one of thiadiazole, 2-bromo-5-fluoro-1,3,4-thiadiazole, 2-bromo-5-chloro-1,3,4-thiadiazole, 2,5-bis(trifluoromethyl)-1,3,4-thiadiazole, 2,5-bis(1,1,2,2,2-pentafluoroethyl)-1,3,4-thiadiazole, and 2,5-bis(1,1,2,2,2-pentafluoroethyl)-1,3,4-thiadiazole.

4. An electrolyte according to claim 1, characterized in that: The mass percentage of the additive in the electrolyte is 0.4-10%.

5. An electrolyte according to claim 1, characterized in that: The mass percentage of the additive in the electrolyte is 0.7-5%.

6. An electrolyte according to claim 1, characterized in that: The lithium salt is any one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium hexafluorophosphate, lithium tetrafluoroborate and organic anion lithium salt.

7. An electrolyte according to claim 1, characterized in that: The lithium salt concentration is 0.1 ~ 6.0 mol / L.

8. An electrolyte according to claim 1, characterized in that: The solvent is propylene carbonate, dimethoxyethane, N,N-dimethylformamide or 1,3-dioxolane.

9. A battery comprising the electrolyte according to any one of claims 1 to 8, characterized in that: It includes positive electrode active material, negative electrode active material and electrolyte, the positive electrode active material is ternary positive electrode material, lithium cobalt oxide positive electrode material, lithium manganese oxide positive electrode material or lithium iron phosphate positive electrode material, and the negative electrode active material is artificial graphite, natural graphite or composite graphite.

10. An electrical device comprising the battery according to claim 9.

Citation Information

Patent Citations

  • Anti-overcharging electrolyte based on ternary lithium ion battery and lithium ion battery

    CN106252725A

  • Lithium secondary battery comprising non-aqueous electrolyte

    CN108028426A

  • Wide-temperature type lithium ion battery non-aqueous electrolytic solution for high voltage, and lithium ion battery

    CN112234252A

  • Non-aqueous electrolyte for lithium ion battery and lithium ion battery

    CN119153779A

  • Nonaqueous electrolyte and lithium secondary battery using it

    JP2003272701A